Saccadic Impairments in Patients with the Norrbottnian Form of Gaucher’s Disease Type 3 - Blume, Josefine; Beniaminov, Stanislav; Kämpe Björkvall, Cecilia; Machaczka, Maciej; Svenningsson, Per (Frontiers in Neurology, 2017)
BACKGROUND: Chronic neuronopathic Gaucher’s disease type 3 (GD3) is relatively frequent in northern Sweden. Besides multiple other neurological symptoms, horizontal gaze palsy or oculomotor apraxia are common in GD3. OBJECTIVE: To characterize the saccades in patients with Norrbottian GD3 in relationship to their neurological and cognitive status using a computer-based eye-tracking technique. METHODS: Horizontal and vertical reflexive saccades as well as antisaccades of nine GD3 patients (4M/5F; 41.1 ± 11.0y; mSST: 9.3 ± 5.4; MoCA: 24.0 ± 4.2) and age-matched controls were analyzed using EyeBrain T2, a head-mounted binocular eye-tracker. Systematic clinical assessment included the modified Severity Scoring Tool (mSST), a valid tool for monitoring the neurological progression in GD3, and Montreal Cognitive Assessment (MoCA). RESULTS: In Norrbottian GD3 patients, gain, peak and average velocity (107.5°/s ± 41.8 vs. 283.9°/s ± 17.0; p=0.0009) of horizontal saccades were reduced compared to healthy controls. Regarding vertical saccades, only the average velocity of downwards saccades was decreased (128.6°/s ± 63.4 vs. 244.1°/s ± 50.8; p=0.004). Vertical and horizontal saccadic latency were increased (294.3ms ±37.0 vs. 236.5ms ± 22.4; p=0.005) and the latency of horizontal reflexive saccades was correlated to the mSST score (R2=0,80; p=0.003). The latency of antisaccades showed association to MoCA score (R2=0.70; p=0.009). GD3 patients made more errors in the antisaccade task (41.5% ± 27.6% vs. 5.2% ± 5.8%; p=0.005) and the error rate tended to correlate to the cognitive function measured in MoCA score (p=0.06). CONCLUSIONS: The mean age of 41 years of our GD3 cohort reflects the increased life expectancy of patients in the Norrbottian area compared to other GD3 cohorts. Marked impairment of horizontal saccades was evident in all patients while vertical saccades showed distinct impairment of downwards velocity. Latency of reflexive saccades was associated to the severity of neurological symptoms. Increased latency and error rate in the antisaccade task were linked to cognitive impairment. The assessment of saccades provides markers for neurological and neuropsychological involvement in Norrbottian GD3.